Efficient Light Trapping in Hexagonal InP Nanostructured Solar Cells Using Plasmonic Al Nanoparticles - Manisha Rautela; Jitendra Kumar (IEEE Journal of the Electron Devices Society)
InP nanostructure based solar cells (SCs) offer the unique potential for reduced material consumption and effective management of light trapping and scattering processes, paving the way for low cost, high efficiency SCs. Effective light trapping is acknowledged as a pivotal factor for further reducing the cost and enhancing the performance of nanostructure based SCs. Consequently, researchers have explored various strategies for light trapping, with surface plasmon resonance (SPR) based optical absorption enhancement using metal nanoparticles (NPs) emerging as a viable approach. However, the impact of Aluminium nanoparticles (Al NPs) on enhancing the efficiency of InP nanowire (NW) SCs has not been studied yet. Hence, In this work, we employed the finite-difference time-domain (FDTD) method to explore the impact of plasmonic Al NPs on SC consisting of hexagonal InP NWs. The localized surface plasmon resonance (LSPR) observed in Al NPs contributes to a substantial enhancement in absorption near the band edge of InP. Our findings demonstrate that, for a low aspect ratio (D/P) of 0.3, optimizing the geometrical characteristics of the Al NPs leads to a 42.68% increase in power conversion efficiency (PCE) and a 50% increase in absorption efficiency at 900 nm for the suggested structure compared to the bare structure. The results can further enhance our understanding of plasmonic NPs and their optimization for SC applications.